2022
DOI: 10.3389/fonc.2022.946257
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome/exome analysis of circulating tumor DNA and comparison to tumor genomics from patients with heavily pre-treated ovarian cancer: subset analysis of the PERMED-01 trial

Abstract: IntroductionThe poor prognosis of ovarian carcinoma (OvC) is due to the advanced stage at diagnosis, a high risk of relapse after first-line therapies, and the lack of efficient treatments in the recurrence setting. Circulating tumor DNA (ctDNA) analysis is a promising tool to assess treatment-resistant OvC and may avoid iterative tissue biopsies. We aimed to evaluate the genomic profile of recurrent heavily pre-treated OvC.MethodsWe performed tumor panel-based sequencing as well as low-coverage whole-genome s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…In Sabatier, R. et al . [ 31 ], the average ctDNA fraction was 12.7%, and all 11 samples with Pearson’s correlation coefficients between ctDNA’s and tumor tissue’s copy number alteration profiles of 0.3 or lower were those with ctDNA fraction of less than 15%. Other studies have speculated that low ctDNA fractions were behind poor data quality [ 32 , 33 ], but the exact ctDNA fractions were not measured or reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Sabatier, R. et al . [ 31 ], the average ctDNA fraction was 12.7%, and all 11 samples with Pearson’s correlation coefficients between ctDNA’s and tumor tissue’s copy number alteration profiles of 0.3 or lower were those with ctDNA fraction of less than 15%. Other studies have speculated that low ctDNA fractions were behind poor data quality [ 32 , 33 ], but the exact ctDNA fractions were not measured or reported.…”
Section: Discussionmentioning
confidence: 99%
“…For tumor DNA detection, as low as 3% ctDNA fraction was reportedly enough [ 17 ]. For mutational load calculation [ 33 ] and copy number alteration analysis [ 31 ], data quality issues began to emerge in samples with low ctDNA fractions. For WES, ctDNA fraction may be an explanation for the wide variation in reported levels of concordance between ctDNA’s and tumor tissue’s mutational profiles [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The AUC of a published model with three exosomal miRNAs for OC diagnosis was 0.8337 ( Chen et al, 2022 ). A French group reported that the plasma sequencing can detect ctDNA 88% OC cases ( Sabatier et al, 2022 ). Comparing with these models, the performance of our TEPOC is higher or comparable.…”
Section: Discussionmentioning
confidence: 99%
“…Although detecting early-stage may improve the prognosis of ovarian cancer, there is currently a large unmet need for diagnostic biomarkers as no screening tools have been proven effective to date ( Siegel et al, 2021 ). Studies have examined the diagnostic performance of other liquid biopsy components, including CTCs (79.4% sensitivity and 92.2% specificity) ( Wang et al, 2022 ), exosomal miRNAs (model AUC = 0.8337) ( Chen et al, 2022 ), and ctDNA (sensitivity = 88%, specificity 80%) ( Passiglia et al, 2018 ; Sabatier et al, 2022 ). Major advantages of TEPs include the extensive interactions between platelets and tumour cells, high availability in the peripheral blood, lack of interference from genomic DNA given their anuclear structure, and ease of isolation.…”
Section: Applications Of Teps In Ovarian Cancermentioning
confidence: 99%